BIOACCESSIBILITY OF α -DICARBONYL COMPOUNDS IN BREADS AND OTHER BAKERY PRODUCTS USING AN IN VITRO STIMULATED GASTROINTESTINAL DIGESTIVE SYSTEMS - Yaman, M.; Ede-Cintesun, E.; Ozgolet, M.; Serdar, E.; Mizrak, O. F.; Yildirim-Servi, E. (PLAPIQUI(UNS-CONICET), 2023)
Digestive system conditions may increase or decrease the formation alpha-dicarbonyl compounds. This study aims to determine the bioaccessibility of glyoxal (GO) and methylglyoxal (MGO) in bakery products under in vitro gastrointestinal conditions. For this purpose breads and bakery products were obtained from bakehouse in Istanbul, Turkey. The amount of GO and MGO in samples ranged between 54.8 to 180.4 mu g /100 g and 45.8 to 220.3 mu g / 100g respectively. After in vitro digestion GO and MGO levels were increased to between 170.4 to 656.8 mu g / 100g and 105.6 to 1220.9 mu g/100 g, respectively. Bioaccessibility of GO and MGO increased up to 727% and 1351% respectively. High increase rates were observed in samples that contain high fat and low moisture contents. We demonstrated that formation of GO and MGO increase under in vitro digestive system conditions. Further studies are needed to extensively investigate the formation mechanism in such foods.
Keywords: Breads; Glyoxal; Methylglyoxal; Bioaccesibility; HPLC; GLYCATION END-PRODUCTS; MAILLARD REACTION-PRODUCTS; PHENOLIC-COMPOUNDS; WHEAT BREAD; GLYCOXIDATION; MECHANISMS; CHEMISTRY; BARLEY; ACIDS; Engineering